Peran Budaya Organisasi dalam Meningkatkan Prestasi Akademik di Sekolah - Asmaul Husna; Maulida Maulida; Nisa Febriyanti Tanjung; Santi Sari Devi Manurung (Pusat Riset dan Inovasi Nasional, 2024)
The role of organizational culture in improving student academic achievement in schools. The research method used involved an analysis of the literature and previous studies highlighting the relationship between organizational culture and academic achievement. The results of the analysis show that building and strengthening organizational culture, such as a clear vision and mission of the school, effective leadership, open communication, community participation, and reward and recognition systems, contribute significantly to improving students' academic achievement. The references used in this article support the importance of a healthy organizational culture in creating a high-achieving and enjoyable learning environment for every student. The implications of these findings emphasize the need for schools to prioritize building a strong organizational culture to improve overall student academic achievement.